2022
DOI: 10.3390/nu14020234
|View full text |Cite
|
Sign up to set email alerts
|

Combined Body Mass Index and Waist-to-Height Ratio and Its Association with Lifestyle and Health Factors among Spanish Children: The PASOS Study

Abstract: Background and Aims: The World Health Organization recommended simultaneous measurement of body mass index (BMI) and waist circumference (WC) and suggested joint use to predict disease risks. The aim of this study was to assess the prevalence of BMI and waist-to-height ratio (WHtR) categories among Spanish children and adolescents, as well as their associations with several lifestyle factors. Methods: Cross-sectional analysis of 8–16-year-old children and adolescents (n = 3772) were included in the PASOS natio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
0
3
0
1
Order By: Relevance
“…On the other hand, there is a high prevalence of overweight and obesity in children and adolescents ( NCD Risk Factor Collaboration, 2017 ; ALADINO, 2020 ; Bibiloni et al, 2022 ; Serra Majem et al, 2003 ), which increases their risk of developing diseases in adulthood ( Umer et al, 2017 ; Migueles et al, 2023 ). Therefore, having physical activity recommendations that are as tailored as possible to the biological circumstances of children and adolescents, as well as promoting programs that aid in meeting these recommendations, can play an essential role in preventing excess body weight in this population ( Gralla et al, 2016 ; Poitras et al, 2016 ; Owens, Galloway & Gutin, 2016 ; World Health Organization (WHO), 2020 ; Chaput et al, 2020 ; García-Hermoso et al, 2021 ; Migueles et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, there is a high prevalence of overweight and obesity in children and adolescents ( NCD Risk Factor Collaboration, 2017 ; ALADINO, 2020 ; Bibiloni et al, 2022 ; Serra Majem et al, 2003 ), which increases their risk of developing diseases in adulthood ( Umer et al, 2017 ; Migueles et al, 2023 ). Therefore, having physical activity recommendations that are as tailored as possible to the biological circumstances of children and adolescents, as well as promoting programs that aid in meeting these recommendations, can play an essential role in preventing excess body weight in this population ( Gralla et al, 2016 ; Poitras et al, 2016 ; Owens, Galloway & Gutin, 2016 ; World Health Organization (WHO), 2020 ; Chaput et al, 2020 ; García-Hermoso et al, 2021 ; Migueles et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, different indices have been developed, such as the Charlson index with a wide clinical evidence-based utility [43]. The Obesogenic Score (ObS) is an index to determine the role of lifestyle and health factors [44,45].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that the development of obesity in children and adolescents is highly related to unhealthy lifestyle behaviors [14,15], including unhealthy dietary habits, insufficient physical activity, and prolonged sedentary behavior [16]. Parents' lifestyle behaviors have also been linked with risk of developing obesity in offspring, where maternal unhealthy diet, less physical activity, smoking, and drinking were found to be with a higher risk of obesity in offspring during early childhood [17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Potential mechanisms involve offspring imitating parental lifestyle behaviors (eg, dietary habits or physical activity behavior) [31,32], and potential effects of parental lifestyles through epigenetic inheritance [33].…”
mentioning
confidence: 99%